ANALISIS PENGARUH MASA KERJA, TINGKAT PENDIDIKAN DAN SISTEM KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT. ANDALAN FAMILI INDONESIA - Suwarno (JUMANT, 2017)
A company that is eperiencing business growth is expected to be able to creat high produktivity, because produktivity level of the company it self that will determine the level of success of company. The largest contribution in the effort to increase the productivity of the company is the ability of the human resourch or labor. Thus, companies need to increase the productivity employes as possible. The research objective was to determine the length of service, level of education and work systems positive and significant impact on employee productivity, both silmutaneusly and partially on PT. Family mainstay indonesia. With these results expressedthitung 2.403 while ttable 1.683 and 0.022 significant, so thitung 2.403<1.683 and significant ttable 0.022>0.05, then HO rejected and HA accepted, stating working period and partial ssignificant influence to work productivity. With this result thitung 3.492 while ttable 1.683 and 0.001 significant, so thitung .492>1.683 and significant ttable 0.001<0.05, then HO HA accepted and rejected, stating the level of education and partial significant effect on work productivity.with this results states thitung 1.271 whilw ttable 1.683 and does not significantly by 0212, so thitung 1,271>1,683 and insignificant ttable 0212<0.05, thebn HO rejected and HA accepted, which states the system work and no ssignificant effect partially on work productivity. Results of testing the hypothesis that the value of F count 34.654>F table 2.62 and significant probability of much less than 0.05 is 0.000<0.05. then reject HO (thank HI). It cant be conclude that the period of employment, education and work system affects silmultaneously on the productivity of labor, so the hypothesis previously received. Adjusted R square.721 numbers that can be called the coefficient of determination in this case means that 72.1% of labor productivity can be obtained and described by work system, work period, level education. While the remaining 100%-72.1%= 28,9% is explained by other factors or variables outside of such incentives, job title, work experience, living expenses and other.